2006
DOI: 10.1159/000106064
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Phase II Study of Docetaxel in Combination with Gefitinib in Gemcitabine-Pretreated Patients with Advanced/Metastatic Pancreatic Cancer

Abstract: Purpose: To evaluate the efficacy and tolerance of the docetaxel/gefitinib combination as second-line treatment in patients with advanced pancreatic cancer. Patients and Methods: Twenty-six patients pretreated with gemcitabine-based chemotherapy were enrolled in the study. Docetaxel (75 mg/m2, i.v.) was administered every 3 weeks for a maximum of 6 cycles and gefitinib (250 mg/day, p.o.) was given continuously. Results: Five (19.2%) patients achieved stable disease. The median duration of disease co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 31 publications
(16 reference statements)
0
24
0
1
Order By: Relevance
“…Several clinical trials have evaluated the safety and efficacy of second-line chemotherapy in this patient population (Klapdor et al, 2000;Mitry et al, 2006;Choi et al, 2014). Guidelines for pancreatic carcinoma currently recommend second-line chemotherapy in selected patients based on the previous publications in which the overall survival is in the range of 3 to 8 months (Demols et al, 2006;Reni et al, 2006;Ignatiadis et al, 2006;Mitry et al, 2006;Boeck et al, 2007;Kulke et al, 2007). Kim et al (2012) analyzed 90 advanced pancreatic adenocarcinoma patients who had received second-line chemotherapy after failure of firstline therapy and they tried to develop a prognostic model to identify patients who would benefit from second-line treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical trials have evaluated the safety and efficacy of second-line chemotherapy in this patient population (Klapdor et al, 2000;Mitry et al, 2006;Choi et al, 2014). Guidelines for pancreatic carcinoma currently recommend second-line chemotherapy in selected patients based on the previous publications in which the overall survival is in the range of 3 to 8 months (Demols et al, 2006;Reni et al, 2006;Ignatiadis et al, 2006;Mitry et al, 2006;Boeck et al, 2007;Kulke et al, 2007). Kim et al (2012) analyzed 90 advanced pancreatic adenocarcinoma patients who had received second-line chemotherapy after failure of firstline therapy and they tried to develop a prognostic model to identify patients who would benefit from second-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine is the primary cytotoxic drug in first-line treatment of pancreatic cancer (Burris et al, 1997;Inal et al, 2012). However, chemotherapy options are limited for patients relapsing following firstline gemcitabine-based treatment (Demols et al, 2006;Reni et al, 2006;Ignatiadis et al, 2006;Boeck et al, 2007;Kulke et al, 2007). So, the role of second-line therapy remains controversial (Choi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Gefitinib was also evaluated, as a second-line treatment, in combination with docetaxel but the combination failed to be active as a salvage treatment after failure of gemcitabinebased chemotherapy (79).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Disappointing data came from taxane combination trials: the docetaxel-gefitinib association in a phase II trial demonstrated no activity as a salvage treatment (79).…”
Section: Second-line Treatmentsmentioning
confidence: 99%
“…Other EGFR tyrosine kinase inhibitors, including gefitinb and lapatinib, have been tested in pilot studies, but failed to demonstrate a clinically significant activity (Brell et al, 2009;Ignatiadis et al, 2006;Safran et al, 2008).…”
Section: Anti-egfr Therapiesmentioning
confidence: 99%